A continuidade institucional do benefício de prestaç\~ao continuada (BPC) como instrumento da seguridade social - Ana Cleusa Serra Mesquita (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This article analyzes the institutional evolution of the Benefício de Prestaç\~ao Continuada (BPC) since its adoption in 1988 and its first regulation in 1993. Based on the theoretical framework of historical institutionalism and the notion of policy paradigm, which guided a historical analysis supported by qualitative methodology (process tracing and content analysis), the work describes the changes in the BPC over three decades and interprets them. It identified a trajectory of institutional stability, that is, alignment of the BPC with the principles of social security, in spite of the successive changes that this policy has undergone. Gradual changes (by layering and drift) are described, which did not modify the policy paradigm. Instead, such incremental changes reinforced the BPC according to the paradigm of social security, consolidating an institutional change initiated in the context of the democratic transition. Even at critical junctures in which the Executive branch tried to break the BPC's trajectory, this effort was unsuccessful, blocked by actors who resisted changing the main rules of the policy. The article also shows that policy feedback was important for the BPC's institutional continuity.
Keywords: H55; 330; historical institutionalism; institutional change; institutional continuity; social security; Benefício de Prestaç\~ao Continuada; income maintenance